Intermitência entre quadros : intertextualidade e tradução intersemiótica na videoarte de Bill Viola = Intermittence within frames: intertextuality and intersemiotic translation in Bill Viola's video art - Vebber, Filipe R., 1986- (2018)
Orientador: Mauricius Martins Farina